Epidemiology and natural history of Pseudomonas aeruginosa airway infections in non-cystic fibrosis bronchiectasis. Issue 2 (18th June 2018) - Woo, Taylor E.; Lim, Rachel; Surette, Michael G.; Waddell, Barbara; Bowron, Joel C.; Somayaji, Ranjani; Duong, Jessica; Mody, Christopher H.; Rabin, Harvey R.; Storey, Douglas G.; Parkins, Michael D.
The natural history and epidemiology of Pseudomonas aeruginosa infections in non-cystic fibrosis (non-CF) bronchiectasis is not well understood. As such it was our intention to determine the evolution of airway infection and the transmission potential of P. aeruginosa in patients with non-CF bronchiectasis. A longitudinal cohort study was conducted from 1986–2011 using a biobank of prospectively collected isolates from patients with non-CF bronchiectasis. Patients included were ≥18 years old and had ≥2 positive P. aeruginosa cultures over a minimum 6-month period. All isolates obtained at first and most recent clinical encounters, as well as during exacerbations, that were morphologically distinct on MacConkey agar were genotyped by pulsed-field gel electrophoresis (PFGE) and multilocus sequence typing (MLST). A total of 203 isolates from 39 patients were analysed. These were compared to a large collection of globally epidemic and local CF strains, as well as non-CF isolates. We identified four patterns of infection in non-CF bronchiectasis including: 1) persistence of a single strain (n=26; 67%); 2) strain displacement (n=8; 20%); 3) temporary disruption (n=3; 8%); and 4) chaotic airway infection (n=2; 5%). Patterns of infection were not significant predictors of rates of lung function decline or progression to end-stage disease and acquisition of new strains did not associate with the occurrence of exacerbations. Rarely, non-CF bronchiectasis strains with similar pulsotypes were observed in CF and non-CF controls, but no CF epidemic strains were observed. While rare shared strains were observed in non-CF bronchiectasis, whole-genome sequencing refuted patient–patient transmission. We observed a higher incidence of strain-displacement in our patient cohort compared to those observed in CF studies, although this did not impact on outcomes. Pseudomonas aeruginosa demonstrates distinct infection patterns in non-cystic fibrosis bronchiectasis http://ow.ly/PnvA30jvZDi